2008
DOI: 10.1088/0953-4075/41/8/085105
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally resolved partial cross sections and asymmetry parameters for nitrogen K-shell photoionization of the NO molecule

Abstract: The vibrationally resolved partial cross sections and asymmetry parameters for the photoionization of the NO molecule producing NO+ N (1s−1) 3Π, 1Π ions in the vibrationally excited states v′ are measured for photon energies between 412 and 419 eV, across the σ* shape resonance region above the N K-shell ionization threshold. The position of the maximum of for the N (1s−1) is observed to move towards the N (1s−1) 3Π and 1Π thresholds in both channels with increasing vibrational excitation in the parent ion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
5
17
0
Order By: Relevance
“…The influence of full Herzberg-Teller type vibronic interaction has been discussed [6] in this context, but more typically approaches based upon treating the parametric dependence of the electronic matrix element upon nuclear geometry have provided understanding. Such investigations have mainly addressed the localized K-edge ionization of diatomic [7][8][9][10][11] and triatomic [12,13] molecules in the vicinity of shape resonances. Only very recently have such case studies extended to consider PADs in larger non-linear polyatomics [14] and/or valence shell ionization.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of full Herzberg-Teller type vibronic interaction has been discussed [6] in this context, but more typically approaches based upon treating the parametric dependence of the electronic matrix element upon nuclear geometry have provided understanding. Such investigations have mainly addressed the localized K-edge ionization of diatomic [7][8][9][10][11] and triatomic [12,13] molecules in the vicinity of shape resonances. Only very recently have such case studies extended to consider PADs in larger non-linear polyatomics [14] and/or valence shell ionization.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies resolving the vibrational spectra of polyatomic molecules are rare because it requires to deal with few tens of electrons and various normal modes of vibration. Most of the vibrational spectra of polyatomic molecules have been calculated by Lucchese et al [19], [20] and C 6 F 6 [20]. Moreover, almost none of the existent methods have been used to explore the photoelectron spectra in the high energy region because it requires a very accurate (and then expensive) description of the highly oscillating continuum wave functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the measured intensity of vibrational transitions is often found deviating from f FC v 0 [1][2][3][4][5][6][7][8][9]. One of the main reasons of the deviations is the dependence of the electronic core !…”
Section: Introductionmentioning
confidence: 99%
“…Recent high-resolution X-ray photoemission studies [6][7][8][9] evidence that in addition to the interferential mechanism there exist other mechanisms invoking deviations of f v 0 from f FC v 0 . Kukk et al [8] has demonstrated violation of the FC principle due to the photoelectron induced recoil at high energy C 1s shell ionization in CH 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation